Factors Associated with Maternal Deaths in Cotonou Hospitals, Benin - Agballa, Gottfried; Sossa, Charles; Aguemon, Badirou; Damien, Georgia Barikissou; Boyi Hounsou, Christelle; Agossou, Christian; Adjibodé, Omer O.; Djossou, Elvire; Tokpanoudé, Ignace; Dossou, Jean-Paul (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Maternal mortality remains a major public health issue in Benin. This study aimed to determine the hospital-based maternal mortality ratio and factors related with maternal deaths. Subjects and Method: We conducted a case-control study over two years from 1st January 2020 to 31 December 2021 in four Cotonou hospitals. It included 264 maternal deaths (case) matched to 264 controls by delivery mode. The dependent variable was the status at discharge. Independent variables included socio-demographic characteristics, gyneco-obstetric information, medical and gynecologic history as well as type of complications. Univariate and multivariate analysis were performed to identify the factors associated with maternal deaths. Results: The hospital-based maternal mortality ratio was 1403 deaths per 100,000 live births. Age superior than or equal to 30 years old (OR= 3.09; 95% CI= 1.52 to 6.41; p=0.002), admission by a referral from public health facility (OR=4.26; 95% CI= 2.60-7.10; p<0.001) or private health facility (OR= 4.52; 95% CI= 2.49-8.38 ; p<0.001); parity between 1 and 3 (OR=2.72; 95% CI= 1.27 to 6.15; p= 0.012), gestational age less than or equal to 31 weeks (OR=3.77; 95% CI= 2.13 to 6.84 ; p<0.001) and the occurrence of non-infectious (OR= 1.94; 95% CI= 1.27 to 2.97; p= 0.002) and fetal complications (OR= 1.98; 95% CI= 1.13 to 3.54; p=0.018) were the factors associated to maternal deaths. Conclusion: Strengthening policies aiming to increase access to modern methods of contraception and safe abortion, improving the referral system, and implementing multifaceted contextualized interventions could contribute to reducing maternal mortality. Keywords: maternal death, maternal mortality, associated factors, Benin. Correspondence:Gottfried Agballa. Department of Public Health; Faculty of Health Sciences, University of Abomey-Calavi, Benin and Department of Biostatistics, Epidemiology, Population and Diseases Control; Centre de Recherche en Reproduction Humaine et en Démographie, Benin. Email: gottfried.agballa@yahoo.fr Telephone number: +22995278136